Metal hypersensitivity after knee arthroplasty: fact or fiction? - Innocenti, Massimo; Vieri, Berti; Melani, Tommaso; Paoli, Tommaso; Carulli, Christian (Acta Biomedica Atenei Parmensis, 2017)
Background and aim of the work: Hypersensitivity to metals in the general population has an incidence of about 15%, and in rising also for the higher number of joint replacements in the last decades. Total Knee Arthroplasty (TKA) represents the most performed orthopaedic procedure during last years, and it seems to be particularly associated with sensitization after surgery. On the other hand, there is a rising amount of patients with painful but well implanted and functioning TKAs: in certain cases, after the exclusion of the most frequent causes of failure, a condition of hypersensitivity may be found, and a revision with anallergic implants is mandatory. The present study is a review of the potential problems related to hypersensitivity in TKA, its possible diagnostic procedures, and the surgical options to date available. Methods: Medical history, patch testing, and other specific laboratory assays are useful to assess a status of metals hypersensitivity before surgery in subjects undergoing a knee replacement, or even after TKA in patients complaining pain in otherwise well implanted and aligned prostheses. However, few groups worlwide deal with such condition, and all proposed diagnostic protocols may be considered still today conjectural. On the other hand, these represent the most updated knowledge of this condition, and may be useful for both the patient and the orthopaedic surgeon. Once assessed a possible or ascertained allergy to metals, several options are available for primary andr revision knee surgery, in order to avoid the risk of hypersensitivity. Results: A review of the recent publications on this topic and an overview of the related aspects has been made to understand a condition to date considered negligible. Conclusions: Hypersensitivity to metals has not to be nowadays considered a “fiction”, but rather a possible preoperative risk or a postoperative cause of failure of TKA. Crucial is the information of patients and the medical history, associated in suspect cases to laboratory testings. Today in the market several knee implants are available and safe for allergic patients undergoing TKA.